Case report: Kaposi hemangioendothelioma of the right upper limb with the Kasabach–Merritt phenomenon: A potentially lethal diagnostic challenge - Belani, Levin; Sapuan, Jamari; Abdullah, Shalimar; Hing, Erica Yee; Loh, C-Khai; Alias, Hamidah (Frontiers in Pediatrics, 2022)
Kaposi hemangioendothelioma (KHE) is a rare vascular neoplasm that presents usually within the first year of life. Because of its rarity and complexity, there is often a delay in diagnosis. KHE could be associated with a life-threatening consumptive coagulopathy named the Kasabach–Merritt phenomenon (KMP). Here, we present the case of a 2-month-old girl who presented with progressive redness and swelling of her right upper limb over 6 weeks. Multiple health practitioners misdiagnosed her condition as an insect bite, cellulitis, and necrotizing fasciitis and gave treatment accordingly, which proved futile. A full blood count revealed bicytopenia of anemia and thrombocytopenia, a normal coagulation cascade, low fibrinogen, and raised D-Dimer levels. The imaging was suggestive of a high-flow vascular tumor likely to be a KHE. Subsequently, she was started on single-agent oral sirolimus with a dose increment to achieve satisfactory therapeutic levels and was treated for 1 year. She successfully completed the treatment regimen and had only transient hypertriglyceridemia, which resolved upon the completion of treatment. Currently, she is in remission 3 years after treatment. Keeping her case as an example, we would like to highlight the potentially lethal misdiagnosis of KHE with KMP, the importance of an early diagnosis of this condition, and the successful treatment outcome with single-agent sirolimus.